METHODS AND TECHNIQUES OF TEACHING RUSSIAN LANGUAGE IN NON-PHILOLOGICAL FIELDS - Yakubova Go'zalxon Maxmudovna (University Research Base, 2024)
This study examines approaches and strategies for teaching Russian outside of the field of philology, highlighting the particular difficulties and advantages that come with teaching a language in a variety of academic settings. The paper explores effective pedagogical strategies catered to the needs of non-philological students by drawing on theoretical frameworks of second language acquisition and pedagogical principles, empirical studies, and case examples. The incorporation of real materials, interactive exercises, task-based learning, content-based teaching, and technology integration are some of the major themes. The paper emphasizes the significance of interdisciplinary collaboration, learner-centered instruction, and cultural competence in optimizing language learning outcomes through a systematic review of the literature and thematic analysis.